1973
DOI: 10.1017/s0043174500027454
|View full text |Cite
|
Sign up to set email alerts
|

Tall Morningglory Germination Response to Herbicides and Temperature

Abstract: Tall morningglory [Ipomoea purpurea(L.) Roth] seeds were germinated at various temperatures and dry weight conversion measured at 24, 48, 72, 96, and 120 hr. Germination and dry weight conversion were slower at the lower temperatures although both occurred. Tall morningglory could germinate and become established over a wide range of temperatures. Some herbicides were effective in reducing germination, and dry weight conversion was reduced most with the dithiocarbamates followed in sequence by the amides, benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
4
13
0
Order By: Relevance
“…At temperatures below 20/12.5, germination was , 10%, whereas at temperatures above 35/25 C the germination was # 20%. The optimum germination occurred between 20/12.5 and 35/25 C. These results were similar to those obtained by Cole and Coats (1973). They observed that germination of tall morningglory occurred from temperatures of 15 to 30 C, with lower germination at $ 35 C. Similarly, germination of other morningglory species, such as Ipomoea hederacea Jacq.…”
Section: Resultssupporting
confidence: 85%
“…At temperatures below 20/12.5, germination was , 10%, whereas at temperatures above 35/25 C the germination was # 20%. The optimum germination occurred between 20/12.5 and 35/25 C. These results were similar to those obtained by Cole and Coats (1973). They observed that germination of tall morningglory occurred from temperatures of 15 to 30 C, with lower germination at $ 35 C. Similarly, germination of other morningglory species, such as Ipomoea hederacea Jacq.…”
Section: Resultssupporting
confidence: 85%
“…Temperatures at which I. hederifolia germinated in greater amount (%) and in a quicker way (IGS) were concentrated in the interval between 23.7 and 30.2ºC for seeds without chemical treatment and between 21.6 and 35ºC for seeds scarified (TABLE 2). Similar results were found by Cole and Coats (1973) for I. purpurea. These authors observed optimal germination between 20 and 30ºC, besides reduction on germination speed and on dry matter transference from cotyledon to root/ hypocotyl when temperatures were below 20ºC.…”
Section: Resultssupporting
confidence: 89%
“…Germination rates of OWCF spores with metsulfuron were less than 0.5% at 0.1 g ai L 21 and 0.0% at higher concentrations, whereas germination rates of OWCF spores exposed to imazapyr, also an ALS inhibitor, were 19% with highest rate (24 g ai L 21 ) tested. Different responses of tall morningglory [Ipomoea purpurea (L.) Roth] germination rates with herbicides of similar chemical structures have been reported (Cole and Coats 1973). These differences between the germination rates of OWCF with two ALS-inhibiting herbicides may also be due to differences in the inert ingredients associated with the metsulfuron-containing product used (Escort XP) that allow metsulfuron to permeate the cell wall.…”
Section: Resultsmentioning
confidence: 99%